Порівняльна оцінка ефективності двох технологічних підходів з проектування та виготовлення робочих решіток циліндра високого тиску турбіни К-330-23,5 - Усатий, Олександр Павлович; Пащенко, Юрій Григорович; Авдєєва, Олена Петрівна (Національний технічний університет "Харківський політехнічний інститут", 2019)
В роботі наведена порівняльна оцінка ефективності двох технологічних підходів з проектування та виготовлення робочих решіток ротора циліндра високого тиску (ЦВТ) турбіни К-330-23,5. Один підхід потребує використання більш удосконаленої, але і більш дорогої технології виготовлення робочих лопаток, використання яких дозволяє отримати більш ефективні робочі решітки ротора ЦВТ. Інший підхід базується на використанні спрощеної технології виготовлення робочих лопаток з меншими витратами на їх виробництво, але їх використання призводить до виникнення додаткових втрат енергії в таких решітках, що веде до зниження ефективності решіток і всієї проточної частини ЦВТ турбіни К-330-23,5.

The purpose of this research is to study and substantiate the possibility of the use of two options of the technology to manufacture blades in order to provide an optimal variant of the flow part for the high pressure cylinder (HPC) turbine K-330-23.5. The methods of comparative analysis have been used for the comprehensive estimation of the advantages and drawbacks of each technology in question used for the design and manufacture of blades. To solve optimization problems we used the methods of multiparametric multicriterion and multilevel optimization of complex engineering objects. These methods are based on the use of the algorithms of experimental design theory, LPτ-sequence, "bee swarm", nonlinear programming, etc. The computation of steam flow in the turbine flow part and water steam properties has been based on the use of the methods of numerical solution of appropriate equation systems. CFD-methods have been used to estimate the efficiency of rotors assembled using the blades that were manufactured based on the technologies of a different level of complexity. The calculated analysis and the optimization research showed that contemporary optimization methodologies used to get optimal flow parts for the HPC of К-330-23.5 turbine allow us to provide highly efficient flow parts for the HPC using the two types of technologies suggested for the manufacture of blades and blades cascades. At the same time, the research done proved that the use of more expensive technology for the manufacture of blades combined with the solution of multiparametric optimization problem provides a high gain both in the efficiency factor and the cylinder power in comparison with a simpler technology used for the manufacturing of blades. The use of contemporary optimization algorithms allows for a considerable increase in the efficiency of the flow parts of steam turbines even if simplified technologies are used to manufacture rotor blades.
A comparative evaluation of the efficiency two technological approaches to the design and manufacture of the blade cascades of high pressure cylinder turbine К-330-23.5
Keywords: ротор турбіни; робочий профіль; робоча лопатка; оптимізація; проточна частина; технологія; turbine rotor; blade profile; blade; optimization; flow part; technology